2010
DOI: 10.2176/nmc.50.309
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Formation and Rupture of an Intracranial Aneurysm 10 Months After Normal Findings on Conventional Magnetic Resonance Angiography in a Patient With No History of Intracranial Lesions -Case Report-

Abstract: A 40-year-old male smoker presented with a ruptured saccular aneurysm that formed de novo 10 months after normal magnetic resonance (MR) angiography findings. Computed tomography of the head at the second admission showed subarachnoid hemorrhage in the interhemispheric fissure and anterior basal cistern. MR and conventional cerebral angiography revealed an aneurysm arising from the anterior communicating artery (AcomA). MR angiography performed 10 months earlier, when he experienced transient loss of conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Previously published case reports suggest a high rate of SAH in rapidly developing de novo aneurysms, especially in hypertensive patients. 24,28,34,37,44 However, other reports suggest a longer time between discovery of the initial aneurysm and discovery of the de novo aneurysm. Yoneoka et al 45 reported on 12 patients with ruptured de novo aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published case reports suggest a high rate of SAH in rapidly developing de novo aneurysms, especially in hypertensive patients. 24,28,34,37,44 However, other reports suggest a longer time between discovery of the initial aneurysm and discovery of the de novo aneurysm. Yoneoka et al 45 reported on 12 patients with ruptured de novo aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal flow produces local changes in blood pressure and wall sheer stress, which lead to endothelial remodeling and consequent changes in aneurysm geometry. [ 8 9 10 37 40 42 47 48 49 50 55 ] Progressive geometric alteration begets further hemodynamic stress, and the cycle of positive feedback propagates aneurysm growth and rupture. In parallel, inflammation and ischemia induce endothelial remodeling and seed aneurysm growth, via collagen and fibrin deposition within the walls, thinning of the domes, vascular smooth muscle deficiency, fibroblasts and leukocytes infiltration, degradation of matrix proteins, and elevated elastase and collagenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several events were regarded as risk factors with the development of de novo aneurysm, such as middle age, female, hypotension, alcohol consumption and subarachnoid hemorrhage [13][14][15]. Although the incidence of de novo aneurysm formation after PAO may be no higher than those patients with clipped aneurysms, some authors considered that PAO itself may contribute to the development of de novo aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…However, hemodynamic changes were regarded as an important contributory factor. Hemodynamic changes were characterized as high wall shear stress (WSS) and high wall shear stress gradient (WSSG) [2,13,14,[16][17][18]. To supply the ipsilateral circulation following PAO, contralateral blood flow was subject to increase, which leaded to high wall shear stress and high wall shear stress gradient mainly in contralateral carotid artery.…”
Section: Discussionmentioning
confidence: 99%